Interpretation as a Means of Overcoming Distance (Slavic Studies, 2024)
Starting from several theoretical premises for the term interpretation that are offered in literary hermeneutics, the purpose of our text is to illustrate those premises in a specific literary text. The analysis is focused on the novel Приглашение на казнь/ Invitation to a Beheading by Russian author Vladimir Nabokov.